Imaging Patterns in Breast Cancer for Women Under 40 Years: A Descriptive Cohort Study - Amal A. Alhaidary (21633410) (2024)
Background and Aim Breast cancer is the most frequently occurring malignant disease in women and remains the leading cause of cancer-related deaths among females worldwide. The aim of this study is to evaluate the imaging findings of breast cancer in women under the age of 40 and analyze their pathological patterns. Method A retrospective study was conducted from 2013 to 2019, involving 120 patients below 40 years of age with pathologically confirmed primary epithelial breast cancers. The data were collected from the electronic records of a tertiary hospital in Riyadh, Saudi Arabia. Mammograms were performed for 115 patients, ultrasounds were conducted for all patients, and MRI scans were carried out for 47 patients. Results All radiological findings and clinical characteristics of the 120 cases were retrieved from our digital-based system. The majority of breast cancer patients (83.4%) were between 30 and 40 years old, and the most common clinical presentation was a mass (45.8%). Out of the 73 patients who underwent genetic tests, 32.9% tested positive for gene mutations. No statistically significant correlation was found between specific age groups and breast composition (P = 0.216), specific mammogram abnormalities such as masses (P = 0.262), or microcalcifications (P= 0.421). Ultrasonography was performed for all patients, with abnormalities detected in only one patient who was diagnosed with Paget’s disease of the nipple. Masses, with or without parenchymal changes, were the predominant feature in 88.3% of cases. Conclusion The imaging findings in breast cancer cases typically involve masses with suspicious features, irregular shape, and spiculated margins on mammograms, and irregular shape with microlobulated or angular margins on ultrasound. MRI features commonly include masses with irregular shape and heterogeneous enhancement. The luminal B subtype was identified as the most prevalent pathological feature, characterized by a high proliferative index (Ki-67%). Other Information Published in: Journal of Epidemiology and Global Health License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s44197-023-00169-2